Fashion in the digital age: exploring metaverse trends, nfts and sustainability - Sena, Taisa Vieira (2023)
The article stems from an exploratory research on the digitalization and virtualization trend in the world and aims to encourage discussion about this phenomenon in fashion, seeking to understand how this process occurred from materials, textile innovations, production processes to its total dematerialization. Dematerialization is accelerated by digital technology, happy and flexible, expanding the migration from products to services, “Tolkinizing” “things”, in short, replacing the tangible with the intangible. As a research methodology, we have netnography and the description of a methodological path that used the internet itself, as a place of data production. As a result, we observed that the insertion of fashion in the digital universe took place first, through different technologies that streamlined the production process, then through its approach to the area of games, followed by the development of digital products (cards, filters, among others) sold as NFTs and their inclusion in the virtual spaces known as the metaverse. This digitization and virtualization of fashion amplifies its ability to stand as a way of highlighting the symbolic element of digital clothing in the interaction of subjects and a reflection of society in which, as a refuge in the virtual environment, it is an increasingly constant reality, participating in the requests that the internet constitutes a space for social interaction, including for fashion.